A comparison of imaging schedules for prostate radiotherapy including online tracking techniques - Baker, A; Fenwick, J; Mayles, W; Syndikus, I; Wong, H (2011)
Background and purpose: Repeat imaging protocols, specifying imaging frequency and action levels for movement correction, can be used to achieve more accurate targeting of the prostate gland during radiotherapy. We have carried out a study comparing the accuracies of online versus off-line correction strategies which use implanted marker seeds to localize the prostate. Material and methods: Data have been analysed for 60 prostate patients, verified using an online imaging technique. Systematic and random errors have been calculated for a daily imaging protocol and for other common imaging schedules. Resource requirements have been assessed for the daily imaging technique by analysing the in-room timings performed on 10 patients. Results: Daily imaging is beneficial for the majority of patients, an online imaging schedule with a 2 mm action level significantly reducing systematic and random errors. The online imaging can be performed with a 2-minute increase in the standard treatment slot. Conclusions: Online imaging tracking techniques can facilitate margin reduction, which may help to reduce rectal toxicities. The impact on departmental time and resource requirements is modest for the online daily tracking technique with marker seeds and kilovoltage planar imaging. © Cambridge University Press 2011.